2022
DOI: 10.3390/biomedicines10061292
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Improvement during Lactation Normalizes miR-26a, miR-222 and miR-484 Levels in the Mammary Gland, but Not in Milk, of Diet-Induced Obese Rats

Abstract: We aimed to evaluate in rats whether the levels of specific miRNA are altered in the mammary gland (MG) and milk of diet-induced obese dams, and whether improving maternal nutrition during lactation attenuates such alterations. Dams fed with a standard diet (SD) (control group), with a Western diet (WD) prior to and during gestation and lactation (WD group), or with WD prior to and during gestation but moved to SD during lactation (Rev group) were followed. The WD group showed higher miR-26a, miR-222 and miR-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Preferential intake of n-3 PUFA may thus modify the m6A RNA methylation status of the β cell via miR-30b-mediated suppression of FTO [ 200 ]. Consumption of the “Cafeteria diet”—a standardized animal model of hypercaloric Western junk food [ 432 ]—during lactation (day 15) in rats, resulted in higher levels of miR-222 in rat milk compared to the miR-222 levels of the control animals [ 433 , 434 ]. Of note, serum exosomes enriched in miR-222 after bone marrow transplantation increased murine β cell proliferation in mice after STZ-induced β cell injury [ 435 ].…”
Section: Perinatal Factors Disturbing Mex Mir-regulated β Cell Homeos...mentioning
confidence: 99%
“…Preferential intake of n-3 PUFA may thus modify the m6A RNA methylation status of the β cell via miR-30b-mediated suppression of FTO [ 200 ]. Consumption of the “Cafeteria diet”—a standardized animal model of hypercaloric Western junk food [ 432 ]—during lactation (day 15) in rats, resulted in higher levels of miR-222 in rat milk compared to the miR-222 levels of the control animals [ 433 , 434 ]. Of note, serum exosomes enriched in miR-222 after bone marrow transplantation increased murine β cell proliferation in mice after STZ-induced β cell injury [ 435 ].…”
Section: Perinatal Factors Disturbing Mex Mir-regulated β Cell Homeos...mentioning
confidence: 99%
“…Interestingly, the offspring of dams fed the obesogenic diet, breastfed with lower levels of miR-26a, and showed a higher expression of Hmag1, Rb1, and Adam17 in retroperitoneal WAT compared to controls [165]. Notably, elevated levels of miR-222 in the mammary gland (at weaning) and in milk (on day 15 of lactation) were also observed in rat dams that were fed a Western diet from one month before gestation until the end of lactation [196]. This dietary condition was also associated with adverse programming effects on offspring [197].…”
Section: Mirnas In Milkmentioning
confidence: 96%
“…This dietary condition was also associated with adverse programming effects on offspring [197]. Interestingly, the implementation of a healthy diet during lactation, which mitigated most of the detrimental programming effects in the offspring [197], also normalized the expression levels of miRNA-222 in both the mammary glands and milk to values of control rats [196].…”
Section: Mirnas In Milkmentioning
confidence: 99%
“…The authors highlighted their possible role in shaping the development of the infant's immune systems and how they are associated with some diseases in both infants and mothers, including breast neoplasms and neonatal jaundice. Related to this aspect, Pomar et al [7] showed that changing the diet of diet-induced obese mice during lactation can reduce the abnormal level of miRNAs in their mammary glands, but not in their milk.…”
Section: Extracellular Mirnasmentioning
confidence: 99%